Lytic Infection of Lactococcus lactis by Bacteriophages Tuc2009 and c2 Triggers Alternative Transcriptional Host Responses - Ainsworth, Stuart (American Society for Microbiology, 2013)
Here we present an entire temporal transcriptional profile of Lactococcus lactis subsp. cremoris UC509.9 undergoing lytic infection with two distinct bacteriophages, Tuc2009 and c2. Furthermore, corresponding high-resolution whole-phage genome tiling arrays of both bacteriophages were performed throughout lytic infection. Whole-genome microarrays performed at various time points postinfection demonstrated a rather modest impact on host transcription. The majority of changes in the host transcriptome occur during late infection stages; few changes in host gene transcription occur during the immediate and early infection stages. Alterations in the L. lactis UC509.9 transcriptome during lytic infection appear to be phage specific, with relatively few differentially transcribed genes shared between cells infected with Tuc2009 and those infected with c2. Despite the apparent lack of a coordinated general phage response, three themes common to both infections were noted: alternative transcription of genes involved in catabolic flux and energy production, differential transcription of genes involved in cell wall modification, and differential transcription of genes involved in the conversion of ribonucleotides to deoxyribonucleotides. The transcriptional profiles of both bacteriophages during lytic infection generally correlated with the findings of previous studies and allowed the confirmation of previously predicted promoter sequences. In addition, the host transcriptional response to lysogenization with Tuc2009 was monitored along with tiling array analysis of Tuc2009 in the lysogenic state. Analysis identified 44 host genes with altered transcription during lysogeny, 36 of which displayed levels of transcription significantly reduced from those for uninfected cells.